Two-Phase Modeling Technology and Subsection Modeling Method of Natural Gas Hydrate: A Case Study in the Shenhu Sea Area - Liu, Fang; Liang, Jinqiang; Lai, Hongfei; Han, Lei; Wang, Xiaoxue; Li, Tingwei; Wang, Feifei (Frontiers in Earth Science, 2022)
It is found that gas hydrate is not only a pore-filling material, but also exists in the form of rock skeleton particles in the reservoir. Therefore, conventional petrophysical modeling method cannot well characterize the physical properties of gas hydrate reservoir. The two-phase modeling technology used in this paper is equivalent medium modeling technology based on BK solid substitution theory and Gassmann fluid substitution theory to simulate hydrate particles in rock skeleton and hydrate filling in pores respectively. The gas hydrate reservoir in Shenhu area is a typical two-phase medium. The forward modeling results show that the gas hydrate two-phase modeling technology can well fit the longitudinal and shear wave velocity information of this medium. At the same time, due to the great difference in physical properties between hydrate layer and its accompanying free gas layer, the two-phase modeling technique is not suitable for free gas layer. Therefore, this paper adopts the segmented modeling method, and only uses the Gassmann fluid substitution theory to establish the equivalent medium model for free gas layer. The practical application shows that the piecewise modeling method can well solve the problem that the physical properties of two sets of reservoirs differ too much, and make the calibration results of forward synthesis records more accurate.